Legal Challenges Limiting Women’s Rights to Research Scholarship: A Comparative Analysis of Nigeria, Uganda and Indonesia - Aidonojie, Paul Atagamen; Kelechi Jude Onwubiko; Okpoko, Mercy Osemudiame; Kelechi, Uzoho; Obieshi Eregbuonye (Journal of Indonesian Constitutional Law, 2025)
It suffices to state that women are key stakeholders in meaningful development and sustainable growth. Concerning this, in education, women possess the capacity and potential to conduct scholarship research, teach, inspire, and mentor students. However, certain factors limit women’s academic rights in Nigeria, Uganda, and Indonesia, thereby negatively affecting scholarship and research. Hence, the study adopts a doctrinal approach, and the data obtained were analysed using descriptive and analytical methods. The study found that women in Nigeria, Uganda, and Indonesia play crucial roles in sustainable education through research, scholarly teaching, nurturing, and mentoring. The study further found that several factors often limit women’s rights to quality education and research scholarship. Some of these factors include limited resources, an ineffective legal framework in championing the cause of women, most especially in Nigeria, cultural and social norms that tend to subject women to domestic housework, and a lack of an academic institutional support system. The study therefore concludes and recommends that to curtail these challenges, women’s rights to academic freedom in Nigeria, Uganda, and Indonesia. There is a need to reform tertiary institutional policies to support women's academic career development. Provide sufficient funding for women in academic, training, and mentorship programs. This study aims to address significant legal and systemic barriers to women's participation in academia in Nigeria, Uganda, and Indonesia. The contribution of this study is a regulatory model designed to promote the fulfilment of women's rights in research and scholarship.